PEMBUATAN ALAT SPIN COATER BERKECEPATAN SUDUT TINGGI BERBASIS ARDUINO UNO - Sofyan Sa'id Atsaurry; Hannif Izzatul Islam; Nida Nabilah; Dendy Handy Saputra; Gagat Mughni Pradipta; Ade Kurniawan; Heriyanto Syafutra; Ardian Arif; Irzaman Irzaman (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
We have managed to create a high corner velocity spin coater based Arduino Uno. This device assisted with brushless motor and infrared sensor as detection of brushless motor rotation. In experiment conducted research corner velocity of brushless motor on input value 1000 rpm, 2000 rpm, 3000 rpm, 4000 rpm, 5000 rpm, 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm, 10000 rpm, 11000 rpm, 12000 rpm, 13000 rpm, 14000 rpm, 15000 rpm,16000 rpm, 17000 rpm, 18000 rpm, 19000 rpm, and 20000 rpm on spin coater. In this research data showed that the corner velocity that measured by spin coater has difference average is 82.67 rpm with tachometer.Keywords: Arduino, Microcontroller, Brushless Motor, PID, Spin Coating.